Problems and prospects of traditional collection and processing of medicinal plant materials; standardisation of material designated as Ajisamat / Tengku Azlan Shah Tengku Mohamad - Tengku Mohamad, Tengku Azlan Shah (2011)
The current practices of collection and processing of herbal materials by traditional practitioners (mostly Malays) in Perak, Malaysia, were reviewed in order to evaluate how these practices could possibly have an impact on the quality of the final products. The documentation was done through a structured interview survey conducted on 56 practitioners selected from each district of Perak. A majority of the selected practitioners were of the older generation. The method of gathering the plant materials combines collection from the wild, small scale cultivation as well as purchasing from grocery shops or other practitioners. The most commonly used plant parts are roots and leaves. The initial processing practices generally involve slicing of the raw materials into smaller pieces, drying under direct sunlight and grinding. The materials are commonly stored loosely packed, unprotected from light or pest. In total these practitioners use 184 types of plant according to their vernacular names. An analysis of the data showed that the plant known as Ajisamat corresponds to two different species from different families - Salacia macrophylla Blume (Celastraceae) and Prismatomeris glabra (Rubiaceae). Therefore pharmacognostical studies were undertaken to determine identity and quality criteria for these plants. Macromorphological inspection of the vegetative parts of the two plants reveals only a slight difference in the arrangement of the petioles. However, a microscopic investigation of the plants roots revealed distinctive anatomical features. Prismatic calcium oxalate crystals and banded paratracheal parenchyma seen in the root section were characteristics of S. macrophylla while P. glabra is characterised by an abundance of raphide crystals in the root. Other features like the differences of vessels diameters and arrangements were also of diagnostic importance for identification of the plants. Some of these characters were also identified in the powder of these plants and proposed for diagnostic purpose.